Hexavalent chromium (Cr6+) removal from wastewater through electrolysis: Influence of Al3+, Fe3+, and Mg2+ ion additives on treatment efficiency - Jayasinghe, Thilini; Amarasooriya, Gayan; Kawakami, Tomonori; Sivalingam, Vasan; Samarakoon, Gamunu (Frontiers in Chemical Engineering, 2025)
IntroductionA type of batch electrolysis system comprising a platinum anode and stainless-steel cathode was investigated for the removal of hexavalent chromium (Cr6+) from synthetic wastewater.MethodsElectrochemical treatment was conducted at a constant current of 0.25 A with NaCl of 1 g/L as the supporting electrolyte.ResultsThe highest Cr6+ removal efficiencies achieved were at 100 mg/L metal ion dosage and an initial Cr6+ concentration of 5 mg/L, yielding removal rates of 56.80% for Fe3+, 49.62% for Al3+, and 30.05% for Mg2+.DiscussionRemoval was attributed to the in-situ formation of metal hydroxides (Al(OH)3, Fe(OH)3, Mg(OH)2), which subsequently enhanced the reduction and immobilization of Cr6+ through co-precipitation, Coulomb forces, and electrostatic adsorption. Further increase in Cr6+ removal efficiency was inhibited at higher initial Cr6+ concentrations due to the saturation of hydroxides, which also exhibited competitive behaviour toward ion adsorption. These results confirm the significant role of multivalent cation additives in increasing the remediation of Cr6+ in the electrochemical system, thus lending support to the theory behind the development of scalable additive-assisted electrochemical water treatment technique.